2009
DOI: 10.1111/j.1365-2486.2009.02135.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil pH across England and Wales in response to decreased acid deposition

Abstract: Analysis of data from the National Soil Inventory of England and Wales obtained between 1978 and 2003 shows widespread increases in soil pH -i.e., soils became less acid -across both countries during the survey period. In general, soil pH increased under all land uses. At least part of the increase and its regional variation could be explained by decreased sulphur deposition from the atmosphere. Changes in liming practices on arable land probably also contributed. The effect of decreased sulphur deposition was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
93
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 20 publications
(35 reference statements)
12
93
1
Order By: Relevance
“…Through experimental data in grasslands these authors reported a rapid recovery response in soil N cycling processes of limestone grassland within 5 years after the cessation of treatments, implying acidifying N inputs (O'Sullivan et al, 2011). This recovery observed in less acidic soils and based on measurements of permanent plots as well as the recovery reported by Kirk et al (2010) in England and Wales are consistent with our findings. This recovery observed in less acidic soils and based on measurements of permanent plots as well as the recovery reported by Kirk et al (2010) in England and Wales are consistent with our findings.…”
Section: Toward a Recovery Time From Acidificationsupporting
confidence: 91%
See 4 more Smart Citations
“…Through experimental data in grasslands these authors reported a rapid recovery response in soil N cycling processes of limestone grassland within 5 years after the cessation of treatments, implying acidifying N inputs (O'Sullivan et al, 2011). This recovery observed in less acidic soils and based on measurements of permanent plots as well as the recovery reported by Kirk et al (2010) in England and Wales are consistent with our findings. This recovery observed in less acidic soils and based on measurements of permanent plots as well as the recovery reported by Kirk et al (2010) in England and Wales are consistent with our findings.…”
Section: Toward a Recovery Time From Acidificationsupporting
confidence: 91%
“…Within the nonacidic forest areas, the significant recent pH increase in eastern France is consistent with the recent decrease in S and, to a lesser extent, N deposi-tion in this region and the increase in base cation as demonstrated by Croisé et al (2005). As reported by Kirk et al (2010) in acidic soils there will be a rise in pH following decreases in acid deposition, until the balance between H + consumption in weathering and H + production in other processes in the soil is restored. This latter was observed at the Central Massif region (central south of France), where the highest sulfur, nitrate, and ammonium deposits were reported in the late 1990s (Croisé et al, 2005) compared with the other French regions.…”
Section: Toward a Recovery Time From Acidificationsupporting
confidence: 78%
See 3 more Smart Citations